Author Correction: Higher ambient synaptic glutamate at inhibitory versus excitatory neurons differentially impacts NMDA receptor activity - Lulu Yao (Nature Portfolio, 2018)
The original version of this Article omitted the middle initial of the author Jesse E. Hanson. This has now been corrected in both the PDF and HTML versions of the Article.